2014
DOI: 10.1007/s00134-014-3298-4
|View full text |Cite
|
Sign up to set email alerts
|

Use of tracheostomy in the PICU among patients requiring prolonged mechanical ventilation

Abstract: There is significant variation in both the frequency and time to tracheostomy between the studied PICUs for patients requiring prolonged mechanical ventilation; among those who received a tracheostomy, the majority did so after two or more weeks of mechanical ventilation. Future studies examining tracheostomy benefits, disadvantages, outcomes, and resource utilization of this patient subgroup are indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
63
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(75 citation statements)
references
References 20 publications
9
63
0
3
Order By: Relevance
“…19 This result was similar to our findings that the number of extubation failures was statistically higher in the late tracheostomy group than the early tracheostomy group. 19 This result was similar to our findings that the number of extubation failures was statistically higher in the late tracheostomy group than the early tracheostomy group.…”
Section: Discussionsupporting
confidence: 92%
“…19 This result was similar to our findings that the number of extubation failures was statistically higher in the late tracheostomy group than the early tracheostomy group. 19 This result was similar to our findings that the number of extubation failures was statistically higher in the late tracheostomy group than the early tracheostomy group.…”
Section: Discussionsupporting
confidence: 92%
“…A study of United Kingdom PICUs found a 2% incidence of tracheostomy; institutional incidence varied from 0.13 to 5.66% (12). Wakeham et al studied tracheostomies in children in PICUs who required mechanical ventilation for ≥3 days (13). They found 6.6% of these patients received a tracheostomy (48% of whom were also discharged on mechanical ventilator support) and significant variation in the use and timing of tracheostomy across units.…”
Section: Discussionmentioning
confidence: 99%
“…As increasing number of high‐grade malignancies are successfully treated with intensive chemotherapy, we envisage that more children will require prolonged ventilatory support during intensive chemotherapy. A recent series indicates tracheostomy rate of 10% in children with a cancer diagnosis who were ventilated for more than 72 h, which is higher than 6% in our cohort. However, tracheostomy in children with high‐risk cancers should be considered carefully as decision for limitation of care may be challenging practically, ethically and emotionally, if the disease progresses with no possibility of a cure or control of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical tracheostomy in children is associated with high incidence (18‐50%) of complications including dislodgement, obstruction, haemorrhage, infection, granuloma formation, and emphysema . It is infrequently performed in Paediatric Intensive Care Unit (PICU) patients compared to adults due to clinicians’ worry about complications associated with the procedure .…”
Section: Introductionmentioning
confidence: 99%